Antimicrobial monoglycerides for swine and poultry applications - Jackman, Joshua A.; Lavergne, Theresia A.; Elrod, Charles C. (Frontiers in Animal Science, 2022)
The development of natural, broadly acting antimicrobial solutions to combat viral and bacterial pathogens is a high priority for the livestock industry. Herein, we cover the latest progress in utilizing lipid-based monoglycerides as feed additives to address some of the biggest challenges in animal agriculture. The current industry needs for effective antimicrobial strategies are introduced before discussing why medium-chain monoglycerides are a promising solution due to attractive molecular features and biological functions. We then critically analyze recent application examples in which case monoglycerides demonstrated superior activity to prevent feed transmission of viruses in swine and to mitigate bacterial infections in poultry along with gut microbiome modulation capabilities. Future innovation strategies are also suggested to expand the range of application possibilities and to enable new monoglyceride delivery options.